Evaluation of Ceramic Membrane Filtration for Alternatives to Microplastics in Cosmetic Formulations Using FlowCam Analysis - Seung Yeon Kim; Soyoun Kim; Chanhyuk Park (Membranes)
The rapid expansion of the cosmetics industry has significantly increased the adoption of alternative microplastics in response to increasingly stringent global environmental regulations. This study presents a comparative analysis of the treatment performance of silica powder and cornstarch—common alternatives for microplastics in cosmetics—using ceramic membrane filtration combined with flow imaging microscopy (FlowCam) to analyze particle behavior. Bench-scale crossflow filtration experiments were performed with commercially available alumina ceramic membranes. By analyzing high-resolution images from FlowCam, the transport and retention behaviors of the two microplastic alternatives were examined by comparing their morphological properties. Despite their similar particle sizes, the cornstarch demonstrated a higher removal efficiency (82%) than the silica (72%) in the ceramic membrane filtration due to its greater tendency to aggregate. This increased tendency for aggregation suggests that cornstarch may contribute to faster fouling, while the stability and uniformity of silica particles result in less fouling. The FlowCam analysis revealed that the cornstarch particles experienced a slight increase in circularity and compactness over time, likely due to physical swelling and aggregation, while the silica particles retained their shape and structural integrity. These findings highlight the impact of the morphological properties of alternative microplastics on their filtration behavior and fouling potential.